2013
DOI: 10.21109/kesmas.v8i3.359
|View full text |Cite
|
Sign up to set email alerts
|

Asupan Yodium, Ekskresi Yodium Urine, dan Goiter pada Wanita Usia Subur di Daerah Endemis Defisiensi Yodium

Abstract: AbstrakRendahnya asupan yodium berhubungan dengan ekskresi yodium urine (EYU) yang tidak normal. Asupan yodium yang terlalu rendah juga menyebabkan kelenjar tiroid tidak mampu mempertahankan sekresi hormon yang adekuat sehingga timbul hipertrofi tiroid yang menimbulkan goiter. Penelitian ini bertujuan menguji hubungan asupan yodium, EYU, dan goiter pada wanita usia subur (WUS) di daerah endemis defisiensi yodium. Penelitian observasional potong lintang ini dilakukan pada 115 WUS di Kecamatan Prambanan Sleman y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Selenium, iron, and vitamin A deficiencies can also exacerbate the effects of iodine deficiency since glutathione peroxidase and deiodinase are selenium-dependent enzymes [ 35 ]. Another study conducted in Prambanan District, Indonesia, which is an agricultural area and an endemic area for iodine deficiency, found that 15.7% of female respondents aged 18–45 years experienced iodine deficiency [ 36 ]. If this condition occurs in pregnant women, it will result in neonatal physical disabilities, mental disabilities, and neurological disorders [ 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium, iron, and vitamin A deficiencies can also exacerbate the effects of iodine deficiency since glutathione peroxidase and deiodinase are selenium-dependent enzymes [ 35 ]. Another study conducted in Prambanan District, Indonesia, which is an agricultural area and an endemic area for iodine deficiency, found that 15.7% of female respondents aged 18–45 years experienced iodine deficiency [ 36 ]. If this condition occurs in pregnant women, it will result in neonatal physical disabilities, mental disabilities, and neurological disorders [ 23 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of hyperthyroidism than hypothyroidism in IDD endemic areas might be caused by Iodine Induced Hyperthyroidism (IIH). This often associated with the use of iodine prophylaxis such as excess of iodine supplementation, high iodine-containing drugs consumption and frequent consumption of iodine fortified food (Mutalazimah et al 2013).…”
Section: Thyroid Function In Subjectsmentioning
confidence: 99%
“…The survey result in Prambanan Sub-district, Sleman Mutalazimah et al Regency, Yogyakarta, Indonesia showed that TGR in women was 13%. Thus, defined as an endemic area of iodine deficiency (Mutalazimah et al 2013). Severe iodine deficiency is the cause of hypothyroidism, mild to moderate iodine deficiency have a higher prevalence of hyperthyroidism.…”
Section: Introductionmentioning
confidence: 99%